Sulfur isotopes of sulfate measurements from a Greenland ice core (1850-2006) - Ursula Jongebloed; Becky Alexander; Jihong Cole-Dai; Andrew Schauer; Carleigh Larrick; Shohei Hattori; Sara Salimi; Shana Edouard; Lei Geng (Arctic Data Center, 2023)
Anthropogenic sulfate aerosols are estimated to have offset sixty percent of greenhouse-gas-induced warming in the Arctic, a region warming four times faster than the rest of the world. However, sulfate radiative forcing estimates remain uncertain because the relative contributions from anthropogenic versus natural sources to total sulfate aerosols are unknown. Here we measure sulfur isotopes of sulfate in a Summit, Greenland ice core from 1850 to 2006 CE to quantify the contribution of anthropogenic sulfur emissions to ice core sulfate. We use a Keeling Plot to determine the anthropogenic sulfur isotopic signature (δ34Santhro = +2.9  0.3 ‰), and compare this result to a compilation of sulfur isotope measurements of oil and coal. Using δ34Santhro, we quantify anthropogenic sulfate concentration separated from natural sulfate. Anthropogenic sulfate concentration increases to 68 ± 7% of non-sea-salt sulfate (65.1 ± 20.2 µg kg-1) during peak anthropogenic emissions from 1960 to 1990 and decreases to 45 ± 11% of non-sea-salt sulfate (25.4 ± 12.8 µg kg-1) from 1996 to 2006. These observations provide the first long-term record of anthropogenic sulfate distinguished from natural sources (e.g., volcanoes, dimethyl sulfide), and can be used to evaluate model characterization of anthropogenic sulfate aerosol fraction and radiative forcing over the industrial era. These data include sulfur isotopes of sulfate measurements from a Greenland ice core from 1850-2006. The preindustrial dataset (1200-1850) is uploaded to the Arctic data center here: doi:10.18739/A2N873162